Development of Nifedipine Timed-release Spansule Dosage form by Extrusion-Spheronization Technology (Asian Journal of Pharmaceutics (AJP), 2017)
Aims: Sustained-release formulations have been widely developed to improve the therapeutic performance of drugs, in particular, to increase pharmacological efficacy and reduce side effects. Developing spansule dosage form of nifedipine using extrusion and spheronization technique provides efficient control of delivery of drugs over the period of 8 h. Nifedipine pellets coated with hydrophilic hydroxypropyl methylcellulose polymer, hydrophobic polymer (ethyl cellulose), and semipermeable polymer (cellulose acetate) to sufficient weight gain. Desired rate of release achieved by of blend of polymers after optimization of variable. Settings and Design: A rotatable central composite design used with five levels and three polymers for 15 formulations. Based on rate of drug release, formulation optimized backward two-factor interaction and polynomial regression equation. Materials and Methods: Initially nifedipine pellets prepared by extruder and spheronizer and later coated up to desired weight gain by conventional coating pan utilizing various polymers. After coating, pilot blend was prepared with all three polymers. In vitro dissolution carried out to find out release rate and percent of dissolution at t95% as dependent variable. Then, optimized formulation compared with market preparation and in vivo animal study done using mice. Results: In vitro dissolution rate of drug indicated the drug release depends on thickness of coat. However, formulation shown considerable release even with higher level of coat thickness with ethyl cellulose because of other two polymers present in the blend dominates the release pattern. The ratio of mixing of pilot blends also a critical factor in developing spansule dosage form. Desired release pattern achieved after equal ratio of mixing polymer pilot blend and optimization of polymer level. Conclusion: The prototype of this formulation design can use for developing spansule dosage form of any drug.